Neuropati Diabetika: Kontribusi Karakteristik Individu, Lama Sakit, Merokok, dan Hiperglikemi - Balgis Balgis; Sumardiyono Sumardiyono; Indraswari Kirana Suri (Jurnal Kesehatan Masyarakat Indonesia, 2022)
Background: Diabetic neuropathy is one of the most common complications. Identification of risk factors associated with the incidence of diabetic neuropathy required for preventive measures. Objective: This study aims to analyze the risk factors associated with the occurrence of diabetic neuropathy such as age, gender, duration of Diabetes mellitus (DM), smoking, and blood sugar levels. Methods: This analytic observational study used the cross-sectional design approach. Subjects of this study were patients with type 2 DM who met the inclusion and exclusion criteria. Sampling was done by purposive sampling with a sample size of 52 persons. The research location is at Kaliwiro Public Health Center. Statistical analysis of research data was carried out univariate and bivariate in the frequency table and Chi Square test. Results: As many as 73% of this study subjects were female, and the age average of 60 years old. As many as  53,85% of subjects have suffered from DM for more than three years. Only seven subjects smoked, 76.92% of subjects have an uncontrolled blood sugar level. Hyperglycemia, only the associated risk factors diabetic neuropathy (p=0.019). Conclusion: The occurrence of diabetic neuropathy was associated with the control of glucose level. Further study on community-based prevention of diabetic neuropathy by blood sugar control is necessary conducted.